Statutory General Anti-Abuse Rule in the Slovak Tax Code: Some Expectations and the Reality of Its Implementation? - Bonk, František; Cakoci, Karin (Public Governance, Administration and Finances Law Review, 2017)
This article aims towards an analysis of the Slovak Statutory General Anti-Abuse Rule (henceforth GAAR) which entered into force under the initiatives of the EU and OECD on 1 January 2014. The article provides an analysis of the particular construction elements of the implemented GAAR with respect to the European Court of Justice (henceforth ECJ) case law and GAAR legislative practice at EU level, which is seemingly, with regard to the Anti-Tax Avoidance Directive GAAR, unstoppable.